2005
DOI: 10.5194/ars-3-331-2005
|View full text |Cite
|
Sign up to set email alerts
|

Noise Considerations of Integrators for Current Readout Circuits

Abstract: Abstract. In this paper the noise analysis of a current integrator is carried out and measures to reduce the overall noise are presented. The effects of various noise sources are investigated and their dependence on the input capacitance and on the gate area of the input transistors of the OTA used for the readout is shown. Both, input capacitance and gate area, should be kept as small as possible. Moreover, the linearity of the integrator is examined. In addition to that, the available application of such sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Observation of the OTA output voltage showed that the signal generated by ionisation chambers can be very noisy. The noise associated with current read out integrators is studied in detail in [24]. A similar analysis resulted in a cumulative noise voltage of 119 µV in frequency band of 1 mHz to 10 GHz at the OTA output.…”
Section: Radioactive Sourcementioning
confidence: 99%
“…Observation of the OTA output voltage showed that the signal generated by ionisation chambers can be very noisy. The noise associated with current read out integrators is studied in detail in [24]. A similar analysis resulted in a cumulative noise voltage of 119 µV in frequency band of 1 mHz to 10 GHz at the OTA output.…”
Section: Radioactive Sourcementioning
confidence: 99%